If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 + 5m = 4m + 36 Reorder the terms: 42 + 5m = 36 + 4m Solving 42 + 5m = 36 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 42 + 5m + -4m = 36 + 4m + -4m Combine like terms: 5m + -4m = 1m 42 + 1m = 36 + 4m + -4m Combine like terms: 4m + -4m = 0 42 + 1m = 36 + 0 42 + 1m = 36 Add '-42' to each side of the equation. 42 + -42 + 1m = 36 + -42 Combine like terms: 42 + -42 = 0 0 + 1m = 36 + -42 1m = 36 + -42 Combine like terms: 36 + -42 = -6 1m = -6 Divide each side by '1'. m = -6 Simplifying m = -6
| 10-4x=-2-8 | | -2(3s-1)-2=2(5s+3)-3 | | w/7-4=13 | | 3x+1.5y+1.5z=204 | | 3+.75x=10+.50x | | X/-2-1=12 | | 8+4x=x+38 | | 5-q=-q-4 | | y=1/2x-8(-6,-17) | | 18/c=-28 | | 150/2=x | | 2-7x=14-9x | | 0=5x^2-11x+2 | | 4k-9=7k | | 30*5=x | | a^4+a^3-9a^2-9a= | | h/2x2/h | | 5r-6=1r+3 | | z=4x-4 | | 0=7h^2+10h+3 | | 7/5x | | 5x+47=-1-3x | | 2x+3x+5=50 | | a+54=180-2a | | 4k-9=7k | | 7-2x=2-4 | | (x^-2/4x^-6)^-2 | | 3x-9/40 | | 1-4k-2=-8k | | 7+-8c-48= | | 7(2x-10)-(5-7x)= | | h1/3-4=13 |